2021
DOI: 10.3103/s0147687421020010
|View full text |Cite
|
Sign up to set email alerts
|

Local Monitoring of Saprotrophic Bacterial Complexes of Urban Soils in Syktyvkar in 2019 and 2020

Abstract: Abundance and diversity of cultivated bacteria in saprotrophic soil complexes were monitored for two years on the territory of one of the large industrial cities of the European North of Russia, Syktyvkar. The analysis was carried out before and after quarantine due to the COVID-19 pandemic. The city of Syktyvkar is characterized by a high population and intensive anthropogenic pressure. According to the total indicators of the current state of the environmental components, it should belong to the tense catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Other urban tropical and temperate locations have also reported high soil Enterococcus spp. concentrations, but these concentrations were four to seven orders of magnitude higher than our study (Glushakova, Lysak, Belov, et al, 2021;Roll & Fujioka, 1997). A Russian study during the COVID-19 pandemic found that soil Enterococcus spp.…”
Section: Soil Fib Concentrations Among Land Usescontrasting
confidence: 81%
See 1 more Smart Citation
“…Other urban tropical and temperate locations have also reported high soil Enterococcus spp. concentrations, but these concentrations were four to seven orders of magnitude higher than our study (Glushakova, Lysak, Belov, et al, 2021;Roll & Fujioka, 1997). A Russian study during the COVID-19 pandemic found that soil Enterococcus spp.…”
Section: Soil Fib Concentrations Among Land Usescontrasting
confidence: 81%
“…A Russian study during the COVID‐19 pandemic found that soil Enterococcus spp. concentrations decreased in urban areas during quarantine, highlighting the importance of human and animal sources in this environment (Glushakova, Lysak, Belov, et al., 2021). Previous streamwater studies from Hilo also found higher Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%